PENGARUH KEPEMIMPINAN, KOMPETENSI DOSEN, PERILAKU BELAJAR, MOTIVASI BELAJAR TERHADAP KUALITAS SOFT SKILL MAHASISWA STIPAS KEUSKUPANG AGUNG KUPANG - Dau, Yoseph Lodowik Deki (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2020)
The focus of this research is to discover whether leadership, lecturer’competence, learning behavior dan learning motivation influence students’ soft skill quality at the Pastoral Institution of Higher Learning of Kupang Archdiocese. This research is also designed for analyzing which of those four variables that becomes the most dominant factor on student’soft skill quality. Research’s population refers to the student at Pastoral Institution of Higher Learning, Kupang Archdiocese, with total of 136 students. Using simple random sampling as the method, this research focuses on 103 respondents. The results of the descriptive statistics analysis showed that the leadership was catagorized as good (72,74 %), lecturers’ competence as good (67,45 %), learning behavior as good (72,37 %), learning motivation was good (73,31 %), and students’ soft skill quality was also catagorized as good (73,50 %). The results of t-test showed that partially leadership (3.307, sig. 0.001 < 0,05), lecturers’ competence (3.395, sig. 0.001 < 0,05), learning behavior (3.255, sig. 0.002 < 0,05), and learning motivation (2.380, sig. 0.006 < 0,05) had a positive and significant effect on the student’ soft skill quality of Pastoral Institution of Higher Learning, Kupang Archdiocese. The results of F-test indicated that simultaneously the four independent variables: leadership, lecturers’ competence, learning behavior and learning motivation (16,778, sig. 0,000 < 0,05) had a positive and significant effect on the student’ soft skill. It is suggested to the management of Pastoral Institution of Higher Learning, Kupang Archdiocese has to make a evaluation on the leadership and lecturer performance, evaluation on the learning behavior, learning motivation and students’ soft skill quality, to make a research of the others factor that influence on students’ soft skill quality, and human resource development. The management of Pastoral Institution of Higher Learning, Kupang Archdiocese and Swasti Sari Institution can do their job and responsibility to improve the leadership quality, lectrurer’ competence, learning behavior, learning motivation and students’ soft skill quality.